Pengaruh Variasi Menu Terhadap Keputusan Pembelian Di Common Space Coffee & Bar Batam - Yovilia Meysie; Tito Pratama; Syafruddin Rais; Rezki Alhamdi (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
The increasing popularity of cafés as social spaces has intensified competition within the culinary industry. One crucial factor influencing consumers’ purchasing decisions is the variety of menu options offered by a business. This study aims to examine the effect of menu variation on purchasing decisions at Common Space Coffee & Bar Batam. The research applies a quantitative approach with a causal associative design. Data were obtained through an online questionnaire distributed via Google Form to 99 respondents selected using a purposive sampling technique, consisting of customers who had made at least two purchases within the last three months. The data were analyzed using the PLS-SEM 3.0 software. The results demonstrate that menu variation has a positive and significant effect on purchasing decisions, indicated by a path coefficient value of 0.970, a t-statistic of 98.309, and a p-value of 0.000. These findings confirm that a greater diversity of menu offerings substantially enhances consumers’ purchasing decisions